Défice cognitivo em sobreviventes de COVID-19 grave - Ana Cláudia Tavares Ferreira (2022)
Introduction: After being admitted to intensive care, survivors of severe COVID-19 disease are at high risk for cognitive impairment, which is associated with difficulties in activities of daily living and return to work, as well as a reduction in their quality of life. This narrative review aims to conduct a synthesis of the existing evidence on the presence of cognitive changes in survivors of severe disease COVID-19 and to identify factors associated with these changes. Materials and Methods: A literature search was conducted in PubMed of original studies on severe COVID-19 and post-hospital discharge cognitive impairment using the keywords: COVID-19, cognitive impairment, cognitive dysfunction, cognitive decline, intensive care unit, critical Illness e critical care. Results: Ten articles were included in this review, most of them prospective and with samples of patients admitted during the first wave of the pandemic. The Montreal Cognitive Assessment(MoCA) was the most used instrument to assess cognitive changes. In these studies, the percentage of survivors with cognitive impairment ranged from 29% to 62% (cut-off point<26/MoCA). For cognitive domains, memory, processing speed and executive function were the most affected. Advanced age, delirium, prolonged sedation and the need for mechanical ventilation were predictors for cognitive impairment. Discussion/Conclusion: This review found that a significant percentage of survivors of severe COVID-19 had cognitive impairment, particularly older survivors, who had delirium, and were sedated and ventilated during this hospital stay. These results point to the need to assess cognitive changes in these survivors and implement therapeutic approaches to optimize their recovery.